2021
DOI: 10.1111/lam.13458
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic antifungal activity of resveratrol with azoles against Candida albicans

Abstract: Candida albicans is one of the most common clinical pathogenic microorganisms and it is becoming a serious health threat, particularly to immunocompromised populations. Drug resistance of Candida species has also frequently emerged, and combination therapy for fungal infections has attracted considerable attention. In this study, we established the Qinling Mountains myxobacterial secondary metabolites library and a synergic assay in combination with ketoconazole against C. albicans was introduced for metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
(58 reference statements)
0
13
0
1
Order By: Relevance
“…Intriguingly, Houillé et al ( 53 ) found that resveratrol derivates has inhibiting effect on Candida albicans and non-albicans Candida (NAC) species in structure- and/or dose-dependent manner. Afterward, studies have revealed that resveratrol could induce Candida albicans apoptosis and have synergistic effect on azoles (an antifungal medicine) against Candida albicans ( 54 , 55 ). These findings suggest that it might be structure- and dose-dependent on the antimicrobial effect of resveratrol and its derivates.…”
Section: Resveratrol and Intestinal Barriermentioning
confidence: 99%
“…Intriguingly, Houillé et al ( 53 ) found that resveratrol derivates has inhibiting effect on Candida albicans and non-albicans Candida (NAC) species in structure- and/or dose-dependent manner. Afterward, studies have revealed that resveratrol could induce Candida albicans apoptosis and have synergistic effect on azoles (an antifungal medicine) against Candida albicans ( 54 , 55 ). These findings suggest that it might be structure- and dose-dependent on the antimicrobial effect of resveratrol and its derivates.…”
Section: Resveratrol and Intestinal Barriermentioning
confidence: 99%
“…where A, B and C represent the ODs of the positive control, drug and negative control, respectively. The MIC 50 was determined as the concentration of tested compounds that inhibits fungal growth by 50% relative to the corresponding drug-free control (Wang et al 2021). The MIC 50 was calculated using the GraphPad Prism 7.0 software.…”
Section: Antifungal Activity Experimentsmentioning
confidence: 99%
“…RSV could also significantly enhance the antifungal susceptibility of two of the three resistant fluconazole C. albicans strains tested. Itraconazole and ketoconazole in combination with RVS were then used against the resistant strain, obtaining antifungal effects; this indicates that when RSV alone is not effective, a combination with other azole drugs is an alternative strategy [ 41 ].…”
Section: Antifungal Activity On Clinical Isolatesmentioning
confidence: 99%